2008
DOI: 10.1253/circj.72.1185
|View full text |Cite
|
Sign up to set email alerts
|

Both Purkinje Cells and Left Ventricular Posteroseptal Reentry Contribute to the Maintenance of Ventricular Fibrillation in Open-Chest Dogs and Swine Effects of Catheter Ablation and the Ventricular Cut-and-Sew Operation

Abstract: he mechanisms of ventricular fibrillation (VF) remain unclear. The mother rotor hypothesis 1,2 appeals to clinicians, because ablation or pacing delivered to the dominant domain might prevent VF from initiating or being maintained. However, whether the mother rotor, observed in small animal hearts, 3 exists in larger animals has not yet been elucidated. Ideker et al [4][5][6] have been reporting that the dominant domain of VF in large animal is located where the left ventricular posterior wall (LVPW) joins the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…We speculate that these activities may either arise from the Purkinje network or be associated with intramural/transmural reentry. 14,20,[22][23][24][25] Our data suggest that both possibilities may be correct.…”
Section: Relationship Of Epicardial Repetitive Activities and Refds Dmentioning
confidence: 62%
“…We speculate that these activities may either arise from the Purkinje network or be associated with intramural/transmural reentry. 14,20,[22][23][24][25] Our data suggest that both possibilities may be correct.…”
Section: Relationship Of Epicardial Repetitive Activities and Refds Dmentioning
confidence: 62%
“…[28][29][30] Fedorov et al reported that hypothermia at 27°C and 17°C results in non-uniform conduction slowing, increased dispersion of repolarization, and shortened WL in isolated rabbit hearts. 28 Using a clinically applicable temperature (30°C), we observed that TH decreased CV, shortened WL, and enhanced APD dispersion and spatial heterogeneity of CT -1 restitution, consistent with the results reported by Harada et al in a 2-dimensional rabbit ventricle at TH (30°C).…”
Section: Electrophysiological Properties During Th (30°c)mentioning
confidence: 99%
“…The discrepancy in the results among experimental studies may partly be attributable to differences in the size of the heart or to differences in species-related electrophysiological properties of the myocardial tissue. In a recent study by Pak et al, 6 destruction of Purkinje fibers by ablation of the posterior papillary muscle and left ventricular posteroseptum attenuated VF inducibility in both dogs and pigs.…”
Section: Role Of Purkinje Fibers In the Maintenance Of Ventricular Fimentioning
confidence: 91%
“…[2][3][4][5][6] The Purkinje fiber system, which plays a critical role in harmonious myocardial contraction and relaxation via its efficient propagation properties and unique geometrical distribution, 7 is naturally worthy of note when discussing a possible source of VF. Because of the conspicuous heterogeneity in the action potential duration of Purkinje fibers compared with the working myocardium, it is likely that this system offers a substrate for reentry to sustain VF.…”
Section: Article P 1803mentioning
confidence: 99%